Roughness Evaluation of the Machined Surface at Interrupted Cutting Process - Malotova, Sarka; Cep, Robert; Cepova, Lenka; Petru, Jana; Stancekova, Dana; Kyncl, Ladislav; Hatala, Michal (Manufacturing Technology Journal, 2016)
The article deals with the evaluation of the roughness of the machined surface, steel ISO C45 and ISO 11CrMo9-10 after machining at interrupted cutting conditions. A regular interrupted cut and irregular interrupted cut can have significant effect on the resulting surface of components. Parameters of roughness were measured on the slats, which was machined with using the interrupted cutting simulator. The slats were gradually machined - 4, 3, 2 and 1 slat for getting irregular interrupted cut. Selected parameters of roughness which were tested; Ra - an average arithmetic deviation, Rq - an average quadratic deviation and Rz - the maximum height of the roughness profile. Experiment took place in cooperation with Faculty of Mechanical Engineering of VSB - TU Ostrava and Faculty of Mechanical Engineering of ZU Zilina - machining in the laboratories of ZU Zilina, Slovak Republic.
Keywords: surface roughness; interrupted cutting; slat test